1999
DOI: 10.2337/diabetes.48.5.1045
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide 1 increases insulin sensitivity in depancreatized dogs.

Abstract: To determine whether glucagon-like peptide (GLP)-1 increases insulin sensitivity in addition to stimulating insulin secretion, we studied totally depancreatized dogs to eliminate GLP-1's incretin effect. Somatostatin was infused (0.8 microg x kg(-1) x min(-1)) to inhibit extrapancreatic glucagon in dogs, and basal glucagon was restored by intraportal infusion (0.65 ng x kg(-1) x min(-1)). To simulate the residual intraportal insulin secretion in type 2 diabetes, basal intraportal insulin infusion was given to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
75
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 16 publications
3
75
0
Order By: Relevance
“…Although originally described as a potent stimulator of glucose-dependent insulin secretion, recent studies [1,2,3,4,5,6,7,8,10,11,12,13] have shown that the intestinal hormone GLP-1 also prevents the onset of diabetes and ameliorates existing diabetes through a mechanism that includes enhancement of beta-cell mass [16,17,18,19,20]. Despite limited evidence that GLP-1 can activate PKB [34], and that PKBα overexpression enhances beta-cell mass in vivo [27,28], no studies have shown whether PKB is essential for GLP-1-induced beta-cell proliferation and/or prevention of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally described as a potent stimulator of glucose-dependent insulin secretion, recent studies [1,2,3,4,5,6,7,8,10,11,12,13] have shown that the intestinal hormone GLP-1 also prevents the onset of diabetes and ameliorates existing diabetes through a mechanism that includes enhancement of beta-cell mass [16,17,18,19,20]. Despite limited evidence that GLP-1 can activate PKB [34], and that PKBα overexpression enhances beta-cell mass in vivo [27,28], no studies have shown whether PKB is essential for GLP-1-induced beta-cell proliferation and/or prevention of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses a variety of anti-diabetic actions that are mediated at the level of the beta cell, as well as in peripheral tissues. These include not only the stimulation of glucose-dependent insulin secretion [3,4,5], but also the inhibition of glucagon release [6,7], gastric emptying [7,8] and food intake [9,10], and possibly also enhancement of insulin sensitivity [11,12]. Consistent with these biological actions, long-term treatment of Type 2 diabetic patients with GLP-1 decreases HbA 1c values and is associated with lower fasting and postprandial glucose concentrations and reduced body weight [13].…”
mentioning
confidence: 99%
“…Several studies have indicated that GLP-1 might have an insulin-independent effect on glucose homeostasis [26][27][28][29][30][31][32], while other researchers suggested that GLP-1 did not acutely affect glucose metabolism independently of insulin [33][34][35][36][37]. These conflicting results may be a consequence of the large variability in the model and methods used: healthy vs diabetic, diabetic hyperglycaemic vs diabetic maintained euglycaemic, clamp vs IVGTT etc.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, results from in vivo studies have been less consistent. GLP-1 (7-36) has been reported to increase glucose uptake during hyperglycaemia and hyperinsulinaemia in diabetic rats [17], pancreatectomized dogs [18] and in Type I (insulin-dependent) diabetic patients [19,20]. In contrast, GLP-1 (7-36) has been reported to have no effect on the insulin action in non-diabetic human subjects [21], in dogs [22] or Type II diabetic patients [23].…”
mentioning
confidence: 99%
“…Repeated measures ANOVA was used to Several factors could account for these discordant results. A positive but small effect on insulin action has most consistently been observed in severely insulin deficient animals or Type I diabetic patients [18,20]. The methods used to assess insulin action also have differed ranging from clamps, to frequently sampled intravenous glucose tolerance tests to prandial infusions of glucose [17,18,19,20,21,22,23].…”
mentioning
confidence: 99%